Evaluating combined effect of different coated urea with PGPR on yield and nitrogen use efficiency in lowland rice by regression model and principal component analysis approach. (21st April 2023) - Sharma, Sachin; Bahuguna, Ayush; Parihar, Manoj; Yadav, Janardan; Singh, Surendra
Abstract: Nitrogen (N) loss is a key problem in rice fields, which results in low nitrogen use efficiency (NUE) of applied N and could be a major limitation from economic and environmental perspectives. In order to improve the NUE, use of slow or controlled released N fertilizers could be a potential alternative to the conventional N inputs. With this objective to evaluate the effect of different slow-release fertilizers on NUE and grain yield of rice, a pot experiment was conducted during kharif 2017 at Department of Soil Science and Agricultural Chemistry, Institute of Agricultural Sciences, Banaras Hindu University Varanasi. The experiment comprised thirteen treatments including control, Polymer (PCU) and Neem coated urea (NCU) and their combination with Farm yard manure (FYM) and Plant growth promoting rhizobacteria (PGPR). The combined application of PCU, NCU, FYM and PGPR in treatment T12 provided highest grain yield 47.98 gpot −1 and followed by T8 46.60 gpot −1 . The result showed that, compared with the PCU treatment T2 (PCU100 Split), the Agronomic efficiency (AE) and Apparent nitrogen recovery efficiency (ANR%) of the mixed doses of coated urea treatment T12 (PCU50 NCU50 FYM10 PGPR Basal) increased by 20.38% and 28.48% respectively. Therefore, application of FYM and PGPR with coated urea improved rice yield, nutrient uptake and their use efficiency and potentially recommended in eastern plain of the Indo-Gangetic Plain for the sustainable production of rice crop.